Operational Management of Ship Guidance PT. Pelabuhan Indonesia II (Persero) Palembang Branch: Pengelolaan Operasional Pemanduan Kapal PT. Pelabuhan Indonesia II (Persero) Cabang Palembang - Austin, Trecy; Ramadhan, M. Nur; Iqrom, Redho Aidil; Ibrahim, Ibrahim (Gayaku Publisher, 2024)
As we know, ship management is an activity carried out to initiate a process in work related to ships. This research aims to understand the operational management of ship guidance at PT. Pelabuhan Indonesia II (PERSERO) branch in Palembang. This company is engaged in the provision of shipping, port services for shipping routes, and docking places for ships. Pilotage is the service provided by a vessel when it is about to dock at a stop. The implementation of ship piloting and towing is governed by the Regulation of the Minister of Transportation of the Republic of Indonesia Number 57 of 2015. This research examines how they manage the operational guidance of ships. The findings in the field are related to delays in processes, lack of punctuality, and various other issues. Various operations in the shipping sector using services are wasted time or inefficient. Researchers use the POAC Theory: planning, organizing, actuating, and controlling. This research has informants, namely; (1) Captain of the Sea Pilot, (2) Captain of the Port Pilot, (3) ship entry staff, (4) customer service staff, and (5) ship agents who frequently use the services. The analysis of research involves data reduction or data summarization, data presentation or the objectives to be achieved, and the formulation of conclusions. The research results indicate that the operational management of ship guidance conducted by PT. Pelabuhan Indonesia II (PERSERO) Palembang Branch, when related to the POAC theory, has not been optimal. The hope is that the company's information sources must continue to be updated. The commitment of the guides and staff must be further enhanced so that they can work collaboratively.